Influence of Production Method Information on Acceptance of Precision-Grown Food Compared to Conventional and Organic Food: The Role of Consumer Innovativeness - Lishan Su; Jason Ellis (Journal of Applied Communications, 2024)
Precision farming is becoming crucial in the ongoing agricultural revolution due to its enhanced economic and ecological sustainability in food production compared to conventional farming. However, only a limited number of studies have focused on consumer acceptance of food produced through precision farming. To address this gap, an online experiment (n = 276) was conducted to investigate how production method information influences consumer beliefs of food quality (i.e., health, sustainability, and safety values), ultimately affecting consumer attitudes and purchase intentions toward precision-grown food. The findings suggest consumers exhibit higher quality beliefs, leading to more favorable attitudes and purchase intentions, toward precision-grown food compared to conventional food. This trend was observed when participants were presented with detailed information about the production methods employed in each farming system. In addition, according to the Elaboration Likelihood Model, our study reveals consumer innovativeness has the potential to amplify positive responses in terms of quality beliefs, attitudes, and purchase intentions toward precision-grown food compared to conventional food. Furthermore, our findings suggest that when detailed production methods are presented, precision-grown food may receive favorable quality beliefs, attitudes, and purchase intentions comparable to those for organic food, regardless of consumer innovativeness.
Keywords: precision farming; organic food; food quality and safety; sustainable agriculture; consumer innovativeness